Pressure-core-based reservoir characterization for geomechanics: Insights from gas hydrate drilling during 2012–2013 at the eastern Nankai Trough. (September 2017) - Yoneda, Jun; Masui, Akira; Konno, Yoshihiro; Jin, Yusuke; Kida, Masato; Katagiri, Jun; Nagao, Jiro; Tenma, Norio
Abstract: Pressure coring and analysis technology has progressed remarkably over the last decade. This technology allows for methane-hydrate-bearing sands, silts, and/or clays to be recovered from the deep-sea gas hydrate reservoir and then maintained in the laboratory within the hydrate stability phase boundary for evaluation and characterization. In this study, a series of pressure-core-based undrained/drained confined compression tests, unconfined (uniaxial) compression tests, isotropic loading and unloading tests, and permeability tests are conducted to investigate and characterize the intact strength, compressibility, and permeability of the gas hydrate reservoir. The consolidation tests and fluid flow tests showed that clayey silt sediments have permeability values of approximately tens of microdarcies, and sandy sediments with and without hydrates have permeability values of tens of millidarcies. The sediment from the bottom of the reservoir, which is sandy in nature with fines, also has permeability values of tens of microdarcies. From previous reports, the undrained shear strength of clayey silt sediments with low gas hydrate saturation is relatively low. Results from the drained shear tests and uniaxial compression tests show the first Mohr−Coulomb failure criteria for natural gas hydrate-bearing sediments, in which both the effective cohesion c ' and the friction angle ϕ ' increase with increasing hydrate saturation. The results indicate in situ existence of pore filling and patchy gas hydrate. Finally, a new failure envelope for hydrate-bearing sediment is proposed that includes both hydrate saturation and confining pressure; it shows a good relation with the experimental results. Highlights: Pressure-core-based geomechanical-hydrological tests is conducted for hydrate-bearing sediments. Sandy sediments with hydrates have permeability values of tens of millidarcies. The first Mohr−Coulomb failure criteria for natural gas hydrate-bearing sediments is established. Both the effective cohesion and the friction angle increase with increasing hydrate saturation.